A Human Rights Perspective on Granting Privileges to Descendants of PKI in Indonesia - Susi Susantijo (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
Human rights, as inherent rights granted to all individuals by virtue of their existence, are enshrined in Law Number 39 of 1999 concerning Human Rights. In Indonesia, human rights remain a critical focus, particularly in addressing past gross human rights violations, which continue to be unresolved despite various regulations, including Presidential Letter Number 2 of 2023 and Presidential Decree Number 17 of 2022. These measures, aimed at non-judicial settlement of past violations, have sparked controversy, particularly regarding their compatibility with MPR Decree Number XXV/MPRS/1966. This research explores the challenges and implications of granting special rights to descendants of the PKI, raising the question of whether they are entitled to such privileges. The granting of these rights has provoked both positive and negative reactions within civil society, with the government's central policy seen as a step toward future improvements. Utilizing a normative legal research methodology, this research analyzes various sources such as books, journals, and newspapers, offering a comprehensive legal analysis. The research concludes that, under the principles of justice, benefit, and legal certainty, the Indonesian state’s provision of special rights to the descendants of the PKI is legally legitimate.